KADAR D-DIMER PLASMA DI STROK ISKEMIK AKUT - Mayke, Yessi; Aman, Adi Koesoema; Anwar, Y. (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Ischemic stroke is a clinical sign of brain dysfunction or tissue damage caused by lack of blood flow to the brain that disrupts theblood and oxygen requirements in the brain tissue. In Indonesia, stroke is the third ranks after heart disease and malignancy. The promptdiagnosis can reduce morbidity and mortality. CT-scan is the gold standard, but it has some limitations that are difficult to recognize theearly signs of ischemia on the first day and the cost of the related treatment is expensive. Because of these limitations, such case requireanother sign that is noninvasive, sensitive, specific, easier and cheaper to detect the presence of thrombus while the cause of ischemicstroke is D-dimer. This study was design to know the diagnostic value of plasma levels of D-dimer of the CT-scan in acute ischemic strokeby determination. A cross-sectional study was conducted, where forty patients with inclusion criteria were taken from The NeurologyDepartment. The research was done at the Department of Clinical Pathology RSUP.H.Adam Malik/FK USU Medan. CT-scan as the goldstandard for the D-dimer examination Plasma levels of D-dimer using latex agglutination method with a cut-off 500/mL. Statisticalanalysis using a 2×2 table to determine the sensitivity, specificity, positive predictive value, negative predictive value, prevalence and thelikelihood ratio. The result found were as follows: sensitivity 77.7%, specificity 53.8%, positive predictive value 77.7%, negative predictivevalue 53.8%, prevalence 67.5%, likelihood ratio positive 1.74 and the likelihood ratio negative 0.43. Based on this study, the level plasmaD-dimer could possibly can be used as an exclusion diagnostic in acute ischemic stroke case.